Research Tales of Numbers: Enhancing Numeracy Skills through Digital Storytelling - Saifi, Sajuddin; Lal, Dori (Indian Journal of Educational Technology, 2024)
The National Education Policy (NEP) 2020 emphasises the importance of foundational numeracy as a key component of early childhood education. The policy recognises that developing strong foundational numeracy skills is essential for building a strong foundation in mathematics and other disciplines and for preparing children for success in the 21st century. To achieve the goal of foundational numeracy we need that pedagogy, which is helpful in developing foundational skills among the learners in grade third. This paper focuses on such pedagogy which is helpful in teaching mathematics, i.e., digital storytelling. For this study, the methodology was a quasi-experimental design, which was conducted over 240 students in grade 3. The results of the control and experimental groups showed a significant difference at 0.5 level when the achievement of the two groups was compared. The results show that digital storytelling is effective in comparison to teaching mathematics in traditional ways.